„Naprawiacze” w Obozie Zjednoczenia Narodowego - Waingertner, Przemysław (Acta Universitatis Lodziensis. Folia Historica, 1999)
After the death of Piłsudski and the dissolution of the Non-party Block of the Co-operation with the Government (BBWR) – in the period of the aggravating decomposition of the post-May camp, the group of „Naprawa” (in the years 1926-1939 known subsequently as: Związek Naprawy Rzeczypospolitej – the Union of the Amendemend of the Republic, Zjednoczenie Pracy Wsi i Miast – the Union of Labour of Villages and Cities, and Związek Działaczy Społecznych – the Union of the Social Activists) – tried to play a role of the programme creating centre concentrating the dispersed Pitsudski’s supporters. In aspring 1937 the „Amendators” supported the founding of the National Unification Camp (OZN) and joint it. The aggravating international situation of Poland convinced them to support the idea of the national consolidation under the leadership of the „successor of the Commander” (Piłsudski) – General Inspector of the Military Forces – Edward Rydz-Śmigły. Initially „Naprawa” proclaiming the necessity of the political dialogue between the Pilsudski’s supporters and the Polish Socialist Party, Polish Peasant Party and Polish Labour Party as well as the idea of the tolerant state policy towards national minorities, played the role of the inner opposition within the OZN. It opposed the national and totalitarian tendencies that dominated in the leading circles of the Camp. In the years 1938-1939 when the personal changes in the leadership of the OZN had been already completed and the political position of the Camp had been shifted into the direction of more moderate state-national ideology, the „Amendators” won quite a considerable influence on the shaping of the programme and the acitivity of the Camp. It seems they considered the OZN as a decadent form of the post-May system of ruling of the country embodied by the authoritarian dictatorship of the Pilsudski’s supporters. They stressed the necessity to democratize in an evolutionary way the political relations in the country. Referring to the slogans of the strong state, stabile democracy and social justice they tried to create the political centre with and ideological programme clear and attractive for the electorate.